Teenage mutant ninja turtles (2011), volume 17 ebook Desperate measures. - Eastman, Kevin (Teenage Mutant Ninja Turtles (2011), 2017)
Alopex is alone, her psyche reeling from Kitsune's mind control. With Raphael and Nobody searching for her, will she be able to find her way back to the side of good? Plus, the government's hunt for mutants begins in earnest and their unconventional tactics will see the TMNT hounded like never before! No mutant is safe! Collects issues #66–70. Author: Tom Waltz, Kevin Eastman. Illustrator: Sophie Campbell, Mateus Santolouco. © 2018 Viacom International Inc. All rights reserved. TEENAGE MUTANT NINJA TURTLES and all related titles, logos, and characters are trademarks of Viacom International Inc. Based on characters created by Peter Laird and Kevin Eastman.